Functional Contribution of Elevated Circulating and Hepatic Non-Classical CD14(+)CD16(+) Monocytes to Inflammation and Human Liver Fibrosis - Zimmermann, Henning W. (Public Library of Science, 2010)
BACKGROUND: Monocyte-derived macrophages critically perpetuate inflammatory responses after liver injury as a prerequisite for organ fibrosis. Experimental murine models identified an essential role for the CCR2-dependent infiltration of classical Gr1/Ly6C(+) monocytes in hepatic fibrosis. Moreover, the monocyte-related chemokine receptors CCR1 and CCR5 were recently recognized as important fibrosis modulators in mice. In humans, monocytes consist of classical CD14(+)CD16(−) and non-classical CD14(+)CD16(+) cells. We aimed at investigating the relevance of monocyte subpopulations for human liver fibrosis, and hypothesized that ‘non-classical’ monocytes critically exert inflammatory as well as profibrogenic functions in patients during liver disease progression. METHODOLOGY/PRINCIPAL FINDINGS: We analyzed circulating monocyte subsets from freshly drawn blood samples of 226 patients with chronic liver disease (CLD) and 184 healthy controls by FACS analysis. Circulating monocytes were significantly expanded in CLD-patients compared to controls with a marked increase of the non-classical CD14(+)CD16(+) subset that showed an activated phenotype in patients and correlated with proinflammatory cytokines and clinical progression. Correspondingly, CD14(+)CD16(+) macrophages massively accumulated in fibrotic/cirrhotic livers, as evidenced by immunofluorescence and FACS. Ligands of monocyte-related chemokine receptors CCR2, CCR1 and CCR5 were expressed at higher levels in fibrotic and cirrhotic livers, while CCL3 and CCL4 were also systemically elevated in CLD-patients. Isolated monocyte/macrophage subpopulations were functionally characterized regarding cytokine/chemokine expression and interactions with primary human hepatic stellate cells (HSC) in vitro. CD14(+)CD16(+) monocytes released abundant proinflammatory cytokines. Furthermore, CD14(+)CD16(+), but not CD14(+)CD16(−) monocytes could directly activate collagen-producing HSC. CONCLUSIONS/SIGNIFICANCE: Our data demonstrate the expansion of CD14(+)CD16(+) monocytes in the circulation and liver of CLD-patients upon disease progression and suggest their functional contribution to the perpetuation of intrahepatic inflammation and profibrogenic HSC activation in liver cirrhosis. The modulation of monocyte-subset recruitment into the liver via chemokines/chemokine receptors and their subsequent differentiation may represent promising approaches for therapeutic interventions in human liver fibrosis.